Pyridine C(sp2)–H bond functionalization under transition-metal and rare earth metal catalysis - Sindhe, Haritha; Reddy, Malladi Mounika; Rajkumar, Karthikeyan; Kamble, Akshay; Singh, Amardeep; Kumar, Anand; Sharma, Satyasheel (Beilstein Journal of Organic Chemistry, 2023)
Pyridine is a crucial heterocyclic scaffold that is widely found in organic chemistry, medicines, natural products, and functional materials. In spite of the discovery of several methods for the synthesis of functionalized pyridines or their integration into an organic molecule, new methodologies for the direct functionalization of pyridine scaffolds have been developed during the past two decades. In addition, transition-metal-catalyzed C–H functionalization and rare earth metal-catalyzed reactions have flourished over the past two decades in the development of functionalized organic molecules of concern. In this review, we discuss recent achievements in the transition-metal and rare earth metal-catalyzed C–H bond functionalization of pyridine and look into the mechanisms involved.
Keywords: C–H functionalization; heterocycles; pyridine; rare earth metal; transition-metal-catalyzed